Diphenyl diselenide and its interaction with antifungals against Aspergillus spp. (25th August 2020) - Melo, Aryse Martins; Poester, Vanice Rodrigues; Trapaga, Mariana; Nogueira, Cristina Wayne; Zeni, Gilson; Martinez, Marife; Sass, Gabriele; Stevens, David A; Xavier, Melissa Orzechowski
Abstract: Given the few antifungal classes available to treat aspergillosis, this study aimed to evaluate the in vitro antifungal activity of diphenyl diselenide (PhSe)2 alone and in combination with classical antifungals against Aspergillus spp., and its in vivo activity in a systemic experimental aspergillosis model. We performed in vitro broth microdilution assay of (PhSe)2  against 32 Aspergillus isolates; and a checkboard assay to test the interaction of this compound with itraconazole (ITC), voriconazole (VRC), amphotericin B (AMB), and caspofungin (CAS), against nine Aspergillus isolates. An experimental model of invasive aspergillosis in mice was studied, and survival curves were compared between an untreated group and groups treated with 100 mg/kg ITC, or (PhSe)2 in different dosages (10 mg/kg, 50 mg/kg and 100 mg/kg). All Aspergillus non- fumigatus and 50% of A. fumigatus were inhibited by (PhSe)2 in concentrations ≤ 64  µ g/ml, with significant differences in MICs between the sections. Synergism or additive effect in the in vitro (PhSe)2  interaction with VRC and CAS was observed against the majority of isolates, and with ITC against the non- fumigatus strains. In addition to the inhibitory interaction, (PhSe)2 was able to add a fungicidal effect to CAS. Survival curves from the systemic experimental aspergillosis model demonstrated that the inoculum caused an acute and lethal infection in mice, and no treatment applied significantly prolonged survival over that of the control group. The results highlight the promising activity of (PhSe)2 against Aspergillus species, but more in vivo studies are needed to determine its potential applicability in aspergillosis treatment. Lay Summary: The activity of diphenyl diselenide (PhSe)2 alone and in combination with itraconazole, voriconazole, and caspofungin, is described against three of the most pathogenic Aspergillus sections. (PhSe)2 may prove useful in therapy of infection in future; further study is required.